SUSTAINABILITY REPORTING´S CONSTRAINTS TO COST-BENEFIT ANALYSIS FOR SOCIAL AND ENVIRONMENTAL ACTIONS - Araujo, Aneide Oliveira; Ramos, Maria da Conceição Pereira (Contextus - Revista Contemporânea de Economia e Gestão, 2015)
This paper examines the contribution of sustainability reports to analyze the costs and benefits of sustainable enterprises’ actions. Therefore, there was a content analysis of Vale do Rio Doce S.A. and Portugal Telecom S.A. Sustainability Reports in 2011 and 2012, respectively. The study shows that both reports clearly demonstrate the commitment and involvement of these companies with social responsibility corporate, compliance with the instructions of the report by the Global Reporting Initiative (GRI), but do not offer subsidies to a cost-benefit analysis of environmentally and socially sustainable actions. Despite the development initiatives grounded in sustainability (economic, social and environmental), this fact draws attention to the efforts in developing business practices in education, communication and economic accounts, social and environmental toward the improvement of sustainability management instruments and effective implementation of corporate social responsibility.